Intervention protocol for reducing antimicrobial dependence in tilapia-dominant-fish farming system in Bangladesh - Rheman, Shafiq; Khor, Laura; Hossain, Sabrina; Delamare-Deboutteville, Jerome; Chadag, Vishnumurthy Mohan (2024)
A One Health Initiative (OHI), “Protecting Human Health through a One Health Approach” aims to protect human, animal and environmental health by detecting, reducing and controlling the outbreak of zoonoses, foodborne diseases and AMR in low and middle-income countries. This Initiative is implemented by the International Food Policy Research Institute (IFPRI), the International Livestock Research Institute (ILRI), the International Water Management Institute, and WorldFish in Africa and Asia. In Bangladesh, WorldFish with ILRI and IFPRI, is working on reducing AMU and the occurrence and distribution of antimicrobial-resistant pathogens of zoonotic importance in aquaculture settings. In this perspective, WorldFish and the OHI CGIAR partners conducted a cross-sectional (CS) and longitudinal (LS) survey in 2023 to collect baseline information regarding AMU and AMR and farming practices of tilapia-dominant framing systems in Bangladesh. It is imperative to implement intervention programs to reduce antimicrobial usage in aquaculture farms in Bangladesh. The broader aim of the intervention program is to evaluate the effects on production and profitability by reducing the dependence on AMU through antimicrobial-sensitive intervention In context to that this report examines several intervention programs commonly applied in animal health sectors to reduce antimicrobial use. It assesses the appropriateness of these identified intervention programs based on the OHI CS and LS survey findings, as well as other relevant research outcomes conducted in Bangladesh in aquaculture sectors. It also aims to propose detail protocols of the intervention program which are identified as suitable in perspective of Bangladesh aquaculture system